2019
DOI: 10.2217/fon-2018-0571
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy: Last Bullet in Platinum Refractory Germ Cell Testicular Cancer

Abstract: Testicular germ cell tumors are chemosensitive with very high cure-rates even in the metastatic setting. However, patients with platinum-refractory and relapsing tumors after autologous stem cell transplant have very poor outcomes despite salvage treatments, and with no effective alternative therapies. Immunotherapy, notably with PD-1 inhibitors, has proven to be very effective in treating various solid tumors. This review summarizes the experience with anti-PD-1 agents (pembrolizumab, nivolumab) in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Consistent with this, there are several case reports in platinum-resistant TGCTs of response to checkpoint inhibitors (reviewed in ref. 31 ); nevertheless, detailed correlation against expression of specific antigens has yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, there are several case reports in platinum-resistant TGCTs of response to checkpoint inhibitors (reviewed in ref. 31 ); nevertheless, detailed correlation against expression of specific antigens has yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of immune checkpoint inhibitors as reported in available case reports and clinical trials is summarized in Table 2. These data are reviewed in the work of Semaan et al (7,44). Briefly, Shah et al reported the clinical response of patients with embryonal cell carcinoma following a single dose of anti-PD-1 immunotherapy.…”
Section: Anti-pd-1/pd-l1 Inhibitors In Tgctsmentioning
confidence: 99%
“…For these patients, the prognosis of the disease is poor, and they are usually treated with novel chemotherapy regimens (5,6). However, despite the existence of numerous new treatment options involving targeted and biological therapies (sorafenib, pazopanib, everolimus, sirolimus/erlotinib, and brentuximab) that have been evaluated in cisplatin-refractory TGCTs, conventional chemotherapy options with limited activity continue to be utilized for these patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…One issue worth considering is that these studies were performed in multiple relapsed unselected populations; finding a reliable biomarker for discriminating the subset of patients that will benefit from such therapies may be the key for clinical success (like demonstrated in some reports, where patients with PD-L1-positive tumors benefited from the combination of anti-PD-1 pembrolizumab with standard chemotherapy [ 182 ]). Immunotherapies may be effective in the treatment of cisplatin-resistant tumors if the right setting is found [ 183 ].…”
Section: Seeking For Novel Treatments Options For Cisplatin-resistmentioning
confidence: 99%